Metrics and QoE assessment in P2PTV applications. (1st January 2013) - Serral-Gracià, René; Yannuzzi, Marcelo; Marin-Tordera, Eva; Martínez Manzanilla, Anny; Masip-Bruin, Xavi
Peer-to-peer (P2P) is a growing technology offering an affordable platform to deploy distributed services and streaming of multimedia content through peer-to-peer television (P2PTV). Nevertheless, to promote such technology it is necessary to provide a solid streaming quality assessment mechanism. In this context, legacy solutions tied to service level agreements are no longer suitable, as for P2P systems, the service consumers become an active part by assisting in the service delivery. To overcome this limitation, we present a generic multi-layer monitoring and management framework to assess the quality of service (QoS) and the quality of experience (QoE) of multimedia traffic in any P2PTV streaming application. We also demonstrate the usefulness of our solution, by analysing the performance of a real streaming application in a P2PTV environment.